RESEARCH NOTES. BUSY STORES AND DEMANDING CUSTOMERS: HOW DO THEY AFFECT THE DISPLAY OF POSITIVE EMOTION? - Rafaeli, A.; Sutton, R. I. (Academy of Management Journal, 1990)
This study replicates and extends our prior research on expressed emotions. We propose that the levels of a store's busyness and customer demand influence the emotions service employees express dur...